Energy storage potential of sprayed α-MoO3 thin films. (16th December 2020) - Deokate, Ramesh J.; Kate, Ranjit; Shinde, Nanasaheb M.; Mane, Rajaram S.
Abstract : Emerging phase pure energy storage electrodes synthesized with controlled morphology endow an enhanced supercapacitor properties. Abstract : Emerging energy storage electrodes synthesized with controlled morphology are of great importance to enhance supercapacitor properties including specific capacitance (SC). In this study, polycrystalline orthorhombic alpha-molybdenum trioxide ( α -MoO3 ) thin films of different morphologies are deposited over a fluorine-tin oxide (FTO) 3D conducting substrate at various deposition temperatures using spray pyrolysis chemical method. The electrochemical properties of the α -MoO3 thin film electrode supercapacitors were performed using cyclic voltammetry and galvanostatic charge/discharge curves recorded at different scan rates and applied current densities. The nanosheet-type α -MoO3 electrode material prepared at 400 °C on envisaging in supercapacitor applications has endowed a specific capacitance (SC) of 1249.2 F g −1 and cycling stability of 85% even after 5000 cycles, suggesting the importance of the α -MoO3 electrode material in energy storage supercapacitor devices. This work affords a morphology engineering method for supercapacitor applications, which can be extended for implications in other technologies including gas sensors, solar cells, and catalysis.